Near Total Parathyroidectomy is Effective Therapy for Tertiary Hyperparathyroidism. Issue 7 (July 2014) - Dewberry, Lindel Krige; Weber, Collin; Sharma, Jyotirmay
Tertiary hyperparathyroidism (3°HPT) is defined as persistent hyperparathyroidism with hypercalcemia after renal transplantation. Near total parathyroidectomy (NTPTX) is the current standard for surgical intervention. The purpose of this study was to identify outcomes of NTPTX. A retrospective review was conducted of surgeries performed between 1994 and 2013. NTPTX resulted in resolution of 96.9 per cent of patients' hypercalcemia at a median follow-up of three years (interquartile range [IQR], 1 to 8). However, 3.1 per cent of patients remained hypercalcemic with a mean calcium of 10.5 ± 0.2 mg/dL. A total of 78.4 per cent of patients had parathyroid hormone (PTH) levels below 250 pg/mL at a median follow-up of two years (IQR, 2 to 8). The remaining 21.6 per cent had a median PTH of 535 (IQR, 345 to 857). PTH levels dropped from a median of 745 (IQR, 285.75 to 1594.25) pg/mL to 97 (IQR, 60 to 285) pg/mL one month post-NTPTX ( P < 0.01). The most frequent complication was transient hypocalcemia in 27.1 per cent of patients, but no patients became permanently hypocalcemic. In the 1-month postoperative period, only one patient had a cardiac complication, and there was 0 per cent all-cause mortality. Glomerular filtration rate fell from 57.9 ± 28.3 mL/min pre-NTPTX to 53.2 ± 27.5 mL/min at 1-year post-NTPTX ( P < 0.01). NTPTX effectively treats hypercalcemia in 3°HPT. However, PTH remains elevated (greater than 250) in 21.6 per cent of patients.